THE INFLUENCE OF WORK DISCIPLINE AND OCCUPATIONAL HEALTH SAFETY (K3) ON EMPLOYEE PERFORMANCE AT PT XYZ PEKANBARU - Anuar, Saiful; Mardan, Jhonni Ardan; Dzikra, Faira Medina; Nefrida, Nefrida; Muin, Mulyani Rody (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
The quality of human resources is the main asset in company development, where work discipline and occupational health and safety (K3) are important factors that influence employee performance. This research aims to analyze the influence of work discipline and K3 on employee performance at PT XYZ Pekanbaru. The research method uses a quantitative approach with a questionnaire survey of 89 employees selected using probability sampling techniques. The results of the regression analysis show that work discipline and K3 have a significant influence on employee performance both partially and simultaneously, with a contribution of 73.3% to employee performance.